Dynamics of the structures and non destructive testing : special topic volume with invited peer reviewed papers only - Karama, Moussa (Trans Tech Publications Ltd, 2011)
With energy costs increasing, the gains to be made from weight-saving are most significant in the aerospace domain, but such gains are clearly also advantageous for road transport and this is even beginning to be recognised in shipbuilding. Consequently, improved reliability and resistance to degradation and durability in severe environments are always important requirements. Thus the development of composites, nano-composites and refractory alloys having specific properties has become a key factor in industrial and technological progress. Another challenge is the recyclability of advanced materials, as reflected by the emergence of projects involving thermoplastic-matrix composite fuselages. Moreover, the incorporation of biopolymers extracted from diverse raw materials can be an interesting alternative route to attaining the objective of 100% biodegradability. The purpose of these topics is to bring together researchers and specialists from universities and industry who are working on new composites and nano-composites, titanium alloys, etc., as well as structural characterisation using destructive or non-destructive testing, numerical analysis and composite processes. Review from Book News Inc.: Destructive and non-destructive testing of composite and nano-composite materials, as well as refractory alloys, has become more important as their use has increased in structural engineering. The ten papers gathered here focus on the traditional topics of reliability and resistance to degradation, as well as newer topics such recyclability and biodegradability. Containing only invited peer reviewed papers, this collection of pieces contains frequent black and white photographs and figures. The spine and cover omit "the" from the title
Keywords: Materials -- Congresses.; Materials -- Technological innovations -- Congresses.; Materials -- Research -- Congresses.; Nondestructive testing -- Congresses.; elektronické knihy; electronic books